Rare occurrence of common filaggrin mutations in Turkish children with food allergy and atopic dermatitis - VARDAR ACAR, Neşe (Turk J Med Sci, 2020)
BACKGROUND/AIM: Filaggrin is a protein complex involved in epidermal differentiation and skin barrier formation. Mutations of the filaggrin gene (FLG) are associated with allergen sensitization and allergic diseases like atopic dermatitis (AD), allergic rhinitis, food allergy (FA), and asthma. The aim of the study is to reveal the frequency of change in the FLG gene and determine the association between FLG loss-of-function (LOF) mutations and FA and/or AD in Turkish children. MATERIALS AND METHODS: Four FLG loss-of-function (LOF) mutations known to be common in European populations were analyzed in 128 healthy children, 405 food-allergic children with or without atopic dermatitis, and 61 children with atopic dermatitis. PCR-RFLP was performed for genotyping R501X, 2282del4, and R2447X mutations; S3247X was genotyped using a TaqMan-based allelic discrimination assay. Results were confirmed by DNA sequence analysis in 50 randomly chosen patients for all mutations. RESULTS: A total of 466 patients [(67% male, 1 (0.7–2.8) years] and 128 healthy controls [59% male, 2.4 (1.4–3.5) years)] were included in this study. Two patients were heterozygous carriers of wild-type R501X, but none of the controls carried this mutation. Three patients and one healthy control were heterozygous carriers of wild-type 2282del4. Neither patients nor controls carried R2447X or S3247X FLG mutations. There were no combined mutations determined in heterozygous mutation carriers. CONCLUSIONS: Although R501X, 2282del4, R2447X, and S3247X mutations are very common in European populations, we found that FLG mutations were infrequent and there is no significant association with food allergy and/or atopic dermatitis in Turkish individuals.